The development of augmented reality framework to enhance students’ motivation - Farah Mohamad Zain; Marini Kasim; Faizahani Ab Rahman; Mohd Faiz Mohd Yaakob (Journal of Education and Learning (EduLearn), 2026)
Previous studies have shown that augmented reality (AR) is an interactive teaching aids that can improve students’ learning motivation. Many studies have discussed AR technology but there are scarce studies on developing AR framework and guideline for teachers. Therefore, the objective of this research is to study the need to develop an AR framework to enhance motivation among students based on Gagne’s nine events of instruction and self-determination theory (SDT). This research employs the design and development research (DDR) method with a blend of quantitative and qualitative in which data was collected via a closed and open questionnaire. The respondents of this research are 35 teachers who are teaching technology course in Kedah, chosen through purposive sampling. The findings revealed the need to develop an AR framework by taking into consideration five main constructs, namely motivation, technology skills, instructional design, AR development tools and types of AR applications. Hence, AR developed using this framework has the potential to enhance student motivation and create effective AR learning experiences for students.